Voltage Regulations in Electrical Systems - Zulfigarov, Asgar (ADA University, 2024)
Voltage regulation challenges are important from both perspectives: the stability of the grid and reliability of power delivery, especially in modern electrical grids that are facing a rapidly increasing share of renewable sources. In this thesis, challenges and possible solutions to voltage regulation issues within the context of the Azerbaijani power grid will be discussed by focusing on advanced technologies of reactive power compensation, hybrid systems, and smart grid automation. Thesis develops and employs a simulation approach using MATLAB to assess voltage-regulating devices and methodologies against peak loading conditions, intense renewable integration, and extreme weather events. The result highlights the importance of sophisticated devices like Static Synchronous Compensators (STATCOM) and Static Var Compensators (SVC) to enhance grid stability. The STATCOM was far more effective at Baku City and other metropolitan areas, reducing voltage recovery times by 40-60%, while SVCs provided economical stabilization for more rural areas like Gobustan. Also, hybrid renewable energy systems that incorporate wind and solar power in synergy with battery storage reduce voltage variations to levels that maintain grid stability even for 70% or higher penetration of renewable energies. The findings point out the absolute need for adaptive approaches to manage such typical fluctuations in renewable energy sources. This underlines modernization research on infrastructure and the use of smart grid technologies in order to tackle the particular challenges Azerbaijan is facing. In fact, long transmission lines connect far-flung renewable energy projects to metropolitan areas and increase voltage instability, creating the need not only for improvement in transmission infrastructure but also for integrating distributed energy generation methodologies. In some cases, smart grid technologies are capable of increasing voltage regulation efficiencies up to 20-30% through real-time monitoring and adaptive control strategies enabled by SCADA systems and machine learning algorithms. These economic analyses confirm, on the whole thesis level, investments in voltage regulation technologies that are feasible both technically and economically. In more detail, all STATCOM and SVC systems have less than one year payback time, while hybrid ones-as Tesla Megapack-could achieve yearly savings up to $25 million annually due to the reduction of renewable energy curtailments. Therefore, automation in smart grids contributes toward better economic and operational efficiencies, which will in turn help Azerbaijan reach its renewable energy targets without conceding on grid stability and reliability. The thesis concludes with actionable recommendations for phase-by-phase deployment of advanced voltage regulation technologies, centered on urban- and rural-specific approaches, hybrid renewable systems, and policy frameworks for leveraged private investment. Further research efforts are thus suggested in order to: continue regional case studies, refine methodologies adopted for the simulations, and review the consistency of national policies with global best practice in terms of promoting a resilient and sustainable energy system. The thesis is supposed to develop a holistic approach to updating Azerbaijan's electric grid, considering the gap between global trends and local needs. The proposed methodology will be oriented in correspondence with the country's priorities in the field of renewable energy sources for the purpose of promoting its goals of energy security, economic growth, and ecological sustainability.
Keywords: Voltage regulation (Electricity) -- Azerbaijan.; Electric power systems -- Stability -- Azerbaijan.; Electric power distribution -- Azerbaijan.; Smart grids -- Azerbaijan.; Renewable energy sources -- Integration -- Azerbaijan.